Comparative analysis of retrosynthesis applications for predicting of pathways for plant Secondary metabolite production - Yonet, Nilay; Yuka, Selcen Ari; Turker, Musa; Yilmaz, Alper (TAYLOR & FRANCIS LTD, 2024)
Secondary metabolites (SMs), organic compounds synthesized by plants, play crucial roles in their own physiology and within their ecological niches, and have extensive usages in industries like pharmaceuticals, cosmetics, and food. Due to the complex nature of these metabolites, utilizing microorganisms has been proposed for their efficient and cost-effective production. In addressing challenges in SM synthesis, retrosynthesis has become essential. Applications such as RetroPath2.0, BioNavi-NP, and RetroBioCat have been developed to predict and design biosynthetic pathways, supporting synthetic biology and metabolic engineering efforts. These applications employ different methodologies to enhance the synthesis of target compounds, yet often face limitations in user-friendliness, functionality, and adaptability. This study evaluates the potential of RetroPath2.0, RetroBioCat, and BioNavi-NP in predicting the production pathways of 11 alkaloids, a class of plant secondary metabolites (PSMs). Through comparative analysis, the efficacy of these applications in proposing alternative production strategies was assessed. Findings highlighted RetroPath2.0's capability in outlining precise production pathways in host organisms, despite some restrictions in its broader practicability. The study also demonstrated the production pathways of dimethyltryptamine, nicotine, and higenamine in non-plant hosts, illustrating the practical uses of these applications.
Keywords: Secondary metabolites; retrosynthesis applications; synthetic biology; metabolic engineering; alkaloid biosynthesis; BIOCHEMICAL REACTIONS; ESCHERICHIA-COLI; HIGENAMINE; BIOSYNTHESIS; ATLAS; Biotechnology & Applied Microbiology